2021
DOI: 10.3390/f12121635
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Spatial Heterogeneity in the Russian Forest Sector: A Multiple Factor Analysis

Abstract: This study explored the regional differences in the forest industry and management via a Multiple Factor Analysis approach. The dataset used comprises all Russian regions and 34 variables that comprehensively describe the situation in the sector. Based on the Multiple Factor Analysis, the variables contributing most to the spatial heterogeneity in Russian forestry were divided into industrial and forestry factors. The regions leading in the development of the timber industry are mainly located in the Northwest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
2
9
0
2
Order By: Relevance
“…Our results also showed that the major reasons why GEP was increasing in most of China's provinces were the effects of variation in price, planting area, and precipitation. Similarly, the findings on population, socialeconomic level, and industry scale for spatial heterogeneity have been proved in other studies (Gordeev et al, 2021;Wang et al, 2021Wang et al, , 2022Zeng and Wang, 2022). In China, the effects of population growth and urbanization were significant.…”
Section: Discussionsupporting
confidence: 68%
“…Our results also showed that the major reasons why GEP was increasing in most of China's provinces were the effects of variation in price, planting area, and precipitation. Similarly, the findings on population, socialeconomic level, and industry scale for spatial heterogeneity have been proved in other studies (Gordeev et al, 2021;Wang et al, 2021Wang et al, , 2022Zeng and Wang, 2022). In China, the effects of population growth and urbanization were significant.…”
Section: Discussionsupporting
confidence: 68%
“…Even though only 44% of Russian timber and logging industry employees work there, it produces 53% of all Russian sawn timber, and its wood reserves amount to 74.7% of the national level. At the same time, the volume of high-value-added products in Asian Russia is still limited, due to the small size of the domestic market and the conjuncture of demand from bordering countries [17]. Meanwhile, the decline in foreign trade with the European Union creates additional development opportunities for the regions of Asian Russia.…”
Section: Discussionmentioning
confidence: 99%
“…The highest volumes are traditionally logged in the regions of Northwestern Russia (Arkhangelsk Oblast, Karelia Republic, Komi Republic, Vologda Oblast), as well as in Siberia (Irkutsk Oblast, Krasnoyarsk Krai). These two macroregions are the leaders of Russian timber industry due to the resource abundance and proximity to the main markets-Scandinavia and China, respectively [17].…”
Section: Imperfect Competition and Spatial Heterogeneity In The Russi...mentioning
confidence: 99%
See 2 more Smart Citations